KAJIAN PEMIKIRAN PENDIDIKAN AL-FARABI DALAM PENDIDIKAN ISLAM KONTEMPORER - Hilmansah, Deden Hilmansah (Jazirah: Jurnal Peradaban dan Kebudayaan, 2023)
This research was motivated by the need to discuss Al-Farabi's thoughts, where discussion of this matter had still barely been brought to the surface, so the researcher conducted research which aimed to find out Al-Farabi's Educational Thoughts in Contemporary Islamic Education. Through descriptive methods using literature studies, it can be concluded that al-Farabi succeeded in reconciling several philosophical teachings such as Plato and Aristotle and also reconciling religion and philosophy, al-Farabi's thought model is a rational religious school, al-Farabi's Islamic educational thought lies in the existence of intention good character which will lead to good morals, al-Farabi's Islamic education curriculum is in line with the high level curriculum of Islamic education, in divine philosophy al-Farabi puts forward the proposition of obligatory al-wujud and possible al-wujud, in prophetic philosophy al-Farabi argues that it is closely the influence of prophets and philosophers in their ability to communicate with fa'al reason, in the state al-Farabi divided the state or government into state, main, ignorant state, the heretical state, the wicked state, and the changed state, then Al-Farabi's educational thought has significant relevance to contemporary Islamic education, its focus on character formation, spiritual values, and practical skills